Developing Recruitment, Training, and Retention Systems in a Culinary MSME: Evidence from Lynn’s Kitchen - Marto Silalahi; Efendi Efendi; Marisi Butarbutar; Erbin Chandra; Onita Sari Sinaga; Julyanthry Julyanthry; Vivi Candra (TGO Journal of Community Development, 2026)
This article reports a community service program that developed an integrated human resource management (HRM) system for a growing culinary MSME, Lynn’s Kitchen. The program addressed typical HR problems in small food businesses, such as informal recruitment, unplanned training, high employee turnover, and low job satisfaction. Over a two-week intensive intervention, the team implemented a structured approach that combined pre-surveys, competency-based recruitment workshops, a five-module staff training program, and a basic employee retention scheme. The intervention resulted in a formal recruitment system with clear job descriptions and competency-based selection steps, a training curriculum that substantially strengthened employees’ knowledge and practical skills, and revised compensation, career path, and engagement practices that improved job satisfaction and reduced projected turnover. At the business level, the integrated HRM system contributed to higher employee productivity, better operational efficiency, and improved customer evaluations. The findings indicate that investing in systematic recruitment, training, and retention practices is a strategic choice for culinary MSMEs that seek to enhance both their human capital and business sustainability.